Health‐related quality of life for normal glycaemia, prediabetes and type 2 diabetes mellitus: Cross‐sectional analysis of the ADDITION‐PRO study. Issue 6 (12th March 2022) - Leal, Jose; Becker, Frauke; Feenstra, Talitha; Pagano, Eva; Jensen, Troels Mygind; Vistisen, Dorte; Witte, Daniel R.; Jorgensen, Marit Eika
Abstract: Aims: We estimated and compared health‐related quality of life for individuals with normal glucose tolerance, prediabetes and diabetes. Methods: Participants in the ADDITION‐PRO study, Denmark, who attended a health assessment between 2009 and 2011, and who completed the 3‐level EuroQoL 5‐dimensions (EQ‐5D‐3L) questionnaire were included. For the present study, they were classified as normal glucose tolerance, prediabetes and diabetes (screen‐detected and known) using the 2019 American Diabetes Association criteria. Prediabetes was defined as impaired fasting glucose, impaired glucose tolerance or HbA1c between 5.7–6.4% (39–47 mmol/mol). EQ‐5D‐3L data were converted into utility scores using Danish and UK values, where '1' equals full health and '0' equals death. Regression models estimated the association between utility and the different glucose health states. Results: The mean EQ‐5D‐3L score in the sample population was 0.86 ± 0.17 (median 0.85, interquartile range 0.76 to 1) using UK values. Almost half of the sample (48%) reported full health with an EQ‐5D score of '1'. Individuals with known diabetes reported the lowest EQ‐5D‐3L utility scores (0.81 ± 0.20), followed by individuals with screen‐detected diabetes (0.85 ± 0.19), prediabetes (0.86 ± 0.17) and normal glucose tolerance (0.90 ± 0.15). The differences were statistically significant for normal glucose and known diabetes relative to prediabetes, after adjusting for sex, age, smoking, BMI and physical activity. These findings also held using Danish values albeit the differences were of smaller magnitude. Conclusions: Having prediabetes and diabetes was significantly associated with lower health‐related quality of life relative to normal glucose tolerance. Our estimates will be useful to inform the value of interventions to prevent diabetes or prediabetes.